A consumer definition of eco-friendly packaging. (10th April 2020) - Nguyen, Anh Thu; Parker, Lukas; Brennan, Linda; Lockrey, Simon
Abstract: Consumers are increasingly concerned about the environmental consequences of packaging. Businesses are under pressure not only from consumers but also from governments to use eco-friendly packaging for their products. However, what consumers perceive to be eco-friendly packaging is still unclear, especially in emerging markets. This study examines consumer perceptions of eco-friendly packaging in the context of packaged food products of Vietnam. The study involved a series of six focus group discussions conducted with a diverse range of consumers. The focus of the discussion was consumer perceptions of eco-friendly packaging, particularly whether or not consumers would adjust their purchase behaviours to be more environmentally friendly. The data analysis procedure was undertaken using inductive manual coding principles associated with interpretivist research. The results indicate that consumer perceptions of eco-friendly packaging can be categorised along three key dimensions: packaging materials, manufacturing technology and market appeal. While consumers have diverse perceptions of eco-friendly packaging, their knowledge is limited and more related to packaging materials (such as biodegradability and recyclability), and market appeal (such as attractive graphic design and good price). Consumers show little knowledge about manufacturing technologies but still desire an eco-friendly manufacturing process. Results also suggest that a consumer-defined eco-friendly package for food products should be visually appealing while satisfying consumers' environmental expectations relating to packaging materials and manufacturing process. We therefore propose a consumer-initiated development of eco-friendly packaging that can be applied for sustainable packaging strategies. Graphical abstract: Thematic map – Consumer perceptions of eco-friendly packaging. Image 1091 Highlights: Eco-friendly packaging is seen in three dimensions relating to materials, technology and appeal. Packaging materials are used by consumers as cues to assess if a package is or is not eco-friendly. Despite little knowledge, consumers express desire for eco-friendly manufacturing processes. Market appeal of eco-friendly packaging is perceived as having attractive design and good price. Consumers welcome eco-friendly packaging only if it satisfies market appeal criteria.